Protein C and antithrombin III levels in children with cyanotic congenital heart disease - Gürsel, Türkiz; Gücüyener, Kıvılcım (The Turkish Journal of Pediatrics, 1988)
Plasma levels of protein C (PC) and antithrombin III (AT III) were measured in 17 children with cyanotic congenital heart disease (CCHD), 18 children with acyanotic congenital heart disease (ACHD) and 15 healthy controls. The mean values of both PC and AT III were found to be significantly lower (p < 0.001) in the children with CCHD than in those with ACHD and the controls. There was no significant (p > 0.05) correlation found between either inhibitor or serum albumin. Both inhibitors were lower in the cyanotic patients with disseminated intravascular coagulation (DIC) than those without DIC. This data suggests that decrease of PC and AT III in children with CCHD is probably secondary to DIC rather than decreased hepatic synthesis. Decrease of these inhibitors of coagulation may enhance tendency to thrombosis in the patients with CCHD.